PROSPECTS OF FISCAL POLICIES IN THE CONDITION OF ECONOMIC INTEGRATION - Allayarov Sukhrob Rustamovich (Scholars Digest Publishing, 2023)
The article discusses the optimization of fiscal policy on the example of the economy of the Republic of Uzbekistan. In order to achieve economic growth and development of the economy, it is necessary to use measures to stimulate and increase the effectiveness of tax policy, in particular the tax on land use.
Keywords: fiscal policy, tax burden, optimization, economic growth.